Development of a Food Frequency Questionnaire for Assessing Habitual Intake of Free Sugar Among Children in Saudi Arabia - Mumena, Walaa Abdullah; Kutbi, Hebah Alawi (Frontiers in Nutrition, 2022)
The World Health Organization emphasizes the urgency to assess and limit the intake of free sugar among individuals in order to prevent several non-communicable diseases. However, data regarding intake of free sugar are lacking in Saudi Arabia and in the Middle East. A reliable valid tool is needed to assess children’s habitual intake of free sugar in Saudi Arabia. Thus, we aimed to develop and validate a food frequency questionnaire (FFQ) that assesses children’s habitual intake of free sugar in Saudi Arabia. In this cross-sectional study, 424 healthy Saudi children ages 6 to 12 years were included using river sampling method. Sociodemographic data and contact information were collected from mothers using an online survey. Dietary data were collected using 24-h dietary recalls (reference method) and a semi-quantitative FFQ through phone interviews. Items and food groups included in the initial draft of the FFQ were adopted from previous work. Content validity was done to the FFQ with total of 12 food groups and 41 food items. Next, a pilot study was conducted to estimate the sample size needed for the study and to ensure that all items reported in the 24-h dietary recalls were included in the final draft of the FFQ. Finally, data were collected to assess the validity and reliability of the FFQ at the population level. Mean intake of free sugar assessed by the FFQ was significantly higher than that assessed by the 24-h dietary recalls. Spearman’s correlation between total free sugar assessed by the FFQ and 24-h dietary recall was positively low (rs= 0.30, p < 0.001). The coefficient alpha indicated an acceptable level of internal consistency (α= 0.74, p < 0.001). Test-retest reliability for total free sugar intake assessed by the FFQ was positively high (rs= 0.82). A slight agreement between added sugar intake assessed by the FFQ and the 24-h dietary recall was seen among the study sample (κ=0.21, p < 0.001). The newly developed FFQ found to be reasonably valid in assessing children’s habitual intake of free sugar in Saudi Arabia. Validating the instrument among older population in Saudi Arabia is warranted.